Buying environmental problems: The invasive potential of imported freshwater turtles in Argentina - Nori, Javier (2016)
In recent years, decision-makers in Argentina have allowed the legal import of thousands of specimens of freshwater turtles. Given their invasive potential, many of the imported species have become established and have spread to other countries. The three most commonly imported species recently have been Graptemys pseudogeographica, Trachemys scripta, and Pseudemys nelsoni, all of them native to North America. This study assessed the invasive potential of these species in Argentina based on (i) bioclimatic envelope models, (ii) distribution of water bodies, (iii) location of the most populated cities, (iv) comparisons between their alien and native climatic niches, and (v) the main ecological traits of those species. The results showed that these species are able to establish viable populations in Argentina, especially T. scripta and G. pseudogeographica. This is because the country offers a large amount of suitable climatic space for these species, in which there are large areas with rivers and other water bodies. The situation is especially problematic in freshwater ecosystems of the north east, as well as in the most populated portion of the country. A range of regulatory policies are suggested, which could help to reduce biodiversity loss and economic impacts in the future.